2019
DOI: 10.3390/w11101983
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Model of Groundwater Dynamics in the Catchment Area of the Zagorska Mrežnica Spring, the Karst Massif of Kapela Mountain

Abstract: The investigation area is located in the world-famous Dinaric karst. This study presents a conceptual model of groundwater dynamics and its interaction with surface waters, extending from the natural water retention of the Drežničko Polje to the spring zone on the far side of the Kapela Mountain range, including a description of the regional groundwater flow in the Zagorska Mrežnica spring zone. The aim of this research was to determine the possibility of an artificial enlargement of the natural retention of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Poorly permeable rocks (dolomites, dolomitized limestones from the Upper Triassic to Lower Cretaceous) have the permeability ranging from 10 −6 to 10 −8 m/s. Flysch complex from the Lower Triassic to Eocene has permeability <10 −8 m/s as mentioned by Buljan et al [6] based on [44]. The groundwater level in Jurassic and Cretaceous limestone corresponds to the nearest surface flows.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Poorly permeable rocks (dolomites, dolomitized limestones from the Upper Triassic to Lower Cretaceous) have the permeability ranging from 10 −6 to 10 −8 m/s. Flysch complex from the Lower Triassic to Eocene has permeability <10 −8 m/s as mentioned by Buljan et al [6] based on [44]. The groundwater level in Jurassic and Cretaceous limestone corresponds to the nearest surface flows.…”
Section: Introductionmentioning
confidence: 95%
“…Due to the hydrogeological complexity of its karstic part, the exact catchment boundaries are difficult to determine. The SW catchment boundary, which represents the contact between the Adriatic Sea and the Danube River basins [3,6,21], and the N boundary in Slovenia are clearly defined with tracing experiments [22,23]. The NE boundary, which corresponds to the contact between the Dinarides and the Pannonian basin, was previously defined by several authors, namely Bura [24], Roglić [25], Herak [26], and Bogunović and Bensa [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of replacing the order of the time series, the same correlogram will be obtained, only of the opposite sign. Cross-correlation analysis was usually performed in karstic catchment (Fronzi et al, 2020;Buljan et al, 2019;Pavlić and Parlov, 2019).…”
Section: Cross-correlation Analysismentioning
confidence: 99%
“…Cross-correlation and cross-spectral analysis of hydrographs in the northern part of the Dinaric karst of Croatia showed that the hydrogeological characteristics of karstic aquifer systems can present more controlling factor related to the runoff regime when compared to climate change influence (Pavlić and Parlov, 2019). Hydrogeology research of the catchment area of the Zagorska Mrežnica spring was focused to the definition of influence related to designing an injection curtain (Buljan et al, 2019), while in the southern part of Dinaric karst different kind of statistical analysis have been used to evaluate the functioning of Rumin springs (Denić-Jukić et al, 2020). In the northern part of Dinaric karst it has been shown that in the Nanoščica River and Ljubljanica River catchment lower summer discharge can be expected which indicates increase of karst river vulnerability and groundwater availability in near future (Sapač et al, 2019).…”
Section: Introductionmentioning
confidence: 99%